Risk stratification of acute respiratory distress syndrome using a PaO2: Fio2 threshold of 150 mmHg: A retrospective analysis from an Indian intensive care unit - Sehgal, Inderpaul Singh (Lung India, 2020)
BACKGROUND: Whether a Pa(O2): Fi(O2) ratio of 150 mmHg could be used to classify patients with acute respiratory distress syndrome (ARDS) as severe or non-severe is unknown. Herein, we study whether Pa(O2): Fi(O2) <150 mmHg could be used as a risk stratification and prediction tool for mortality in patients with ARDS. METHODS: Patients with ARDS (Pa(O2): Fi(O2) ratio ≤300 mmHg) were categorized as nonsevere ARDS (150≤Pa(O2): Fi(O2) ratio ≤300 mmHg) and severe ARDS (Pa(O2): Fi(O2) ratio <150 mmHg). We compared the physiological characteristics, ventilatory parameters, and mortality between the two groups. Further, we subcategorized those with severe ARDS as very severe (Pa(O2): Fi(O2) ratio ≤100 mmHg) or severe ARDS (100<Pa(O2): Fi(O2) ratio <150 mmHg). We also compared the performance of this cut off value with the Berlin criteria using the receiver operating characteristic curve. RESULTS: Four hundred and sixty (256, non-severe ARDS; 204, severe ARDS) patients (mean standard deviation age, 40 (17) years, 55% males) with ARDS were included. Patients with severe ARDS had significantly lower baseline pH and higher Pa(CO2). Patients with severe ARDS also had higher plateau pressure, peak airway pressure, applied positive end-expiratory positive pressure. The odds ratio (95% confidence interval [CI]) of mortality in those with severe ARDS was 1.6 (95% CI, 1.1–2.4). Although the AUC for both the revised and Berlin models was low, on a multivariate logistic regression analysis, after adjusting for age, gender, sequential organ failure assessment score, driving pressure, and mechanical power, Pa(O2): Fi(O2) ratio of 150 mmHg remained an independent risk for mortality. CONCLUSIONS: The Pa(O2): Fi(O2) ratio threshold of 150 mmHg may be used to identify severe ARDS. However, used alone a Pa(O2): Fi(O2) threshold of 150 mmHg has poor sensitivity in predicting mortality. Due to the small sample, the results of our study should be confirmed in a larger multicentric study.